EFECTO DE LA APLICACIÓN DE ESTRADIOL Y PROGESTERONA SOBRE LA SUPERVIVENCIA EMBRIONARIA EN LLAMAS - Palomino C., Jesús (2012)
The effect of exogenous oestradiol and progesterone on embryonic survival around the period of maternal recognition of pregnancy was evaluated in 80 adult llamas with ³15 days after parturition. An ultrasound evaluation was conducted to detect a preovulatory follicle (³7mm), and then, animalswere matedwith a male for ³15 minutes of copulation time.Animals were allocated into 4 groups: G0, placebo;G1, 0.2mg/llama/day of estradiol; G2, 15mg/llama/day of proligestone, andG3, 0.2mg/llama/day of estradiol and 15 mg/llama/day of proligestone. Injection of hormones and placebo was done at days 8 and 9 after copula. Mating daywas considered as day 0. Ultrasound evaluations were done on day 2 to determine ovulation, on day 9 to measure the size of the corpus luteum, and on days 20, 25, 30 and 35 to observe the presence of the embryonic vesicle and the embryo. Sexual behaviour was evaluated to verify female receptivity on day 0 and to diagnose earlypregnancy on day15. Embryonic survival was higher in G1 (75%) as compared to other groups:G0 (57.9%), G2 (52.6%), and G3 (55.0%) until day 35, but without significant differences. The size of corpus luteumon day9was larger in pregnant (12.8mm) than in non pregnant llamas (10.8mm). In conclusion, the results suggested that the application of estradiol between days 8 and 9 aftermatingmay improve embryonic survival rate in llamas.